Semi-systolic Algorithm Synthesis for the Grid - Okuda, Kunio; Gubitoso, Marco Dimas (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2000)
The systolic paradigm that appeared in the late seventies has contributed to parallel computing in two ways: the development of the method allowed the parallelization of nested loops algorithms and at the same time several practical applications like cryptography and multimedia using mostly 2-d grids. Unifying these two tendencies we propose a new method for semi-systolic algorithm syntesis, for uniform nested loops. Our solution is better than the tradicional approach if the target architecture is a grid.